2016
DOI: 10.1177/1098612x16634388
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of two raw diets vs a commercial cooked diet on feline growth

Abstract: Objectives The objective of this study was to determine if two raw feline diets were nutritionally adequate for kittens. Methods Twenty-four 9-week-old kittens underwent an Association of American Feed Control Officials' (AAFCO) 10 week growth feeding trial with two raw diet groups and one cooked diet group (eight kittens in each). Morphometric measurements (weight, height and length), complete blood counts, serum chemistry, whole blood taurine and fecal cultures were evaluated. Results Overall, the growth par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 13 publications
(13 reference statements)
0
5
1
Order By: Relevance
“…Nevertheless, the two toxigenic C. difficile strains isolated in the present study were recovered from dogs fed RMBD (Table 1). Our results differ from that of a study in kittens, which reported that C. difficile toxins were more likely to be detected in cats from the raw diet group [64]. Another recent study also showed a significant decrease in the C. difficile isolation rate in dogs and cats when fed with dry food [65].…”
Section: Clostridioides Difficilecontrasting
confidence: 99%
“…Nevertheless, the two toxigenic C. difficile strains isolated in the present study were recovered from dogs fed RMBD (Table 1). Our results differ from that of a study in kittens, which reported that C. difficile toxins were more likely to be detected in cats from the raw diet group [64]. Another recent study also showed a significant decrease in the C. difficile isolation rate in dogs and cats when fed with dry food [65].…”
Section: Clostridioides Difficilecontrasting
confidence: 99%
“…Another cat‐feeding trial compared a commercial raw diet, a supplemented raw chicken diet and a tinned diet (Hamper et al ). Kittens of sequential litters from the same two parents grew similarly on any of the diets, clinical pathology analyses showed minor variations, and diarrhoea was encountered with both raw and cooked diets.…”
Section: Evidence Concerning the Benefits Of Raw Feedingmentioning
confidence: 99%
“…Indeed, owners may resort to raw feeding following unhappy experiences with conventional foods that are marketed as ‘hypoallergenic', but that are formulated without sufficient or appropriate source restrictions. The two peer‐reviewed studies in this field that performed prospective comparisons of stool consistency did not show significant differences in the incidence of episodic diarrhoea among dogs or kittens fed raw diets v processed diets (Lefebvre and others 2008, Hamper and others 2017).…”
Section: Proposed Advantages Of Raw Feedingmentioning
confidence: 94%